P130 Intestinal ultrasound combined to fecal calprotectin is effective to predict endoscopic mucosal healing in ulcerative colitis: a cross-sectional study. (30th January 2023) - Yzet, C; Meudjo, E; Moreau, C; Brazier, F; Hautefeuille, V; Decrombecque, C; Sarba, R; Pichois, R; Meynier, J; Fumery, M
Abstract: Background: In the "treat-to-target" era, the development of non-invasive markers to assess endoscopic healing in ulcerative colitis (UC) is essential. Fecal calprotectin (FC) and intestinal ultrasound (IUS) are alternatives to colonoscopy to assess UC activity. The objective of this study was to evaluate the performance of IUS and FC to assess endoscopic mucosal healing in UC patient. Methods: All consecutive patients between January 2021 and August 2022 with UC who underwent (1) a complete colonoscopy (2) an intestinal ultrasound and/or (3) a fecal calprotectin (4) within 4 weeks were included in a prospective cohort. Bowel wall thickness (BWT) and color doppler signal (CDS) were assessed on each segment. Endoscopic mucosal healing was defined by a MAYO score of 0-1. Results: A total of 57 patients were included, 57.9% had endoscopic healing (22/57 MAYO 0 and 11/57 MAYO 1). Thirty-two (56.1%) were female, the median age and disease duration were respectively 43 years (IQR, 30-58) and 29 years (IQR, 18-39). Respectively 16 (16/57, 28.1%) and 41 (41/57, 71.9%) patients had BWT < 3 mm and an absence of Doppler signal. The sensitivity (Se), specificity (Sp), positive predictive value (PPV) and negative predictive value (NPV) of BWT < 3 mm to predict endoscopic mucosal healing were 37%, 77%, 72% and 44%. The association of the absence of CDS with normal BWT did not modify these performances. The same values for fecal calprotectin < 150 µg/g were respectively 81%, 78%, 84% and 74%. The association of a fecal calprotectin < 150 µg/g, with a BWT < 3mm and the absence of Doppler signal increased the specificity and the PPV (Se 33%, Sp 94%, PPV 89%, VPN 48%). The same values were found for patients classified as MAYO 0 or MAYO 0-1 (Table 1). Conclusion: The combination of intestinal ultrasound and fecal calprotectin is effective to identify endoscopic mucosal healing in UC.